Bulgaria - Integrated State-Owned Enterprises Framework (iSOEF) Assessment - World Bank (Washington, DC, 2022)
Bulgaria's transition to a market economy involved massive privatizations over the past few decades, however the central government still retains a portfolio of State-Owned Enterprises (SOEs) which includes some of the largest companies in terms of assets and revenues and dominates strategic sectors such as energy and transport. This report applies the new World Bank integrated State-Owned Enterprises Framework (iSOEF) to assess the Bulgarian state-owned enterprise (SOE) sector and help to identify ways to strengthen its corporate governance and performance. The report provides one of the first comprehensive applications of the World Bank's new iSOEF in Eastern Europe. The report outlines the SOE landscape in Bulgaria and then assesses two key aspects: SOEs fiscal impact and their corporate governance and accountability mechanisms. Leveraging World Bank expertise, this multidimensional assessment looks at the interrelationships of the challenges and opportunities faced by Bulgarian SOEs to propose holistic and sequenced recommendations that aim to strengthen governance and performance. The primary audience of the iSOEF assessment is the government of the Republic of Bulgaria, in particular the Ministry of Finance, the Ministry of Economy and Industry, the Public Enterprises and Control Agency (PECA), and other relevant stakeholders.